China's March to Prosperity Reforms to Avoid the Middle-income Trap - Koen, Vincent 1960- (OECD Publishing, 2013)
China is well-placed to avoid the so-called "middle-income trap" and to continue to converge towards the more advanced economies, even though growth is likely to slow from near double-digit rates in the first decade of this millennium to around 7% at the 2020 horizon. However, in order to sustain vigorous growth and improve the well-being of most citizens, renewed reform momentum is required in a number of areas. The following ones are discussed in this paper: financial sector liberalisation; strengthening competition in markets for goods and services; education, research and innovation. Progress is also needed in other areas, notably in fostering more socially-inclusive forms of urbanisation and more environmentally-friendly growth
Keywords: Economics; China, People's Republic